«Attractive» Adverbials as an Expressive Syntax Method in Copyright (Proceedings of Southern Federal University. Philology, 2020)
In the framework of modern linguistics, the problem of identifying the stylistic, structural-semantic and communicative-pragmatic aspects of the study of the linguistic components of copywriting is discussed. The subject of the study is the «attractive» for the target audience adverbial modifier of manner, a distinctive feature of which is the mechanism of advertising influence on the recipient and the expression of creative strategies of a professional copywriter.Keywords: copywriting, advertising text, expressive syntax, communicative pragmatics, «positive» circumstances.DOI 10.18522/1995-0640-2020-1-103-110